A bat-shape piezoresistor electronic stethoscope based on MEMS technology. (December 2019) - Wang, Weidong; Xu, Qingda; Zhang, Guojun; Lian, Yuqi; Zhang, Lansheng; Zhang, Xiaoyong; Shi, Yiming; Duan, Sicun; Wang, Renxin
Highlights: Design of a MEMS electronic stethoscope with working bandwidth 20–811 Hz. The feasibility of electronic stethoscope is proved with theory and experiment. Test on this electronic stethoscope is found that basically consistent with the 3 M. The SNR of the electronic stethoscope is higher than 3 M. Abstract: In this paper, a bat-shape electronic stethoscope based on MEMS technology is presented. The detector microstructure in bat-shape electronic stethoscope is designed by combining theoretical analysis and finite element method. Visual heart sound signal processing includes circuit and upper computer design. The frequency of the clinical heart sound signal is mostly in the range of 20–600 Hz. The sensitivity of the microstructure, its work-bandwidth and the SNR of the system are the key points of this design. And the final test results showed that the sensitivity of the sensor is −180.7 dB@500 Hz and SNR is 38 dB (17 dB higher than the 3 M electronic stethoscope). Based on theoretical analysis and test results, the bat-shape MEMS electronic stethoscope designed in this paper features small size, high sensitivity, high SNR and easy processing, and has broad prospects in the field of heart sound detection.